Assessing Physiotherapists' Knowledge of Professional Ethics Codes in Shiraz: A Cross-Sectional Study - Marzieh Mohamadi; Hossein Mahmoodian; Narges Meftahi; Zahra Rahmanian (Shiraz University of Medical Sciences, 2024)
Background: Understanding the principles of professional ethics is crucial for physiotherapists as it equips them to navigate ethical dilemmas effectively. This study aimed to assess the awareness level of physiotherapists in Shiraz regarding the ethical principles outlined in the codes of professional ethics within the field of physiotherapy. Method: To carry out this cross-sectional study, a checklist comprising 20 items was developed and distributed to 163 physiotherapists practicing in Shiraz. Each item was scored using a 5-point Likert scale. The checklist allowed for a maximum score of 100 and a minimum score of 20. Results: Out of the 163 physiotherapists approached, 109 completed the checklist. The mean score this study's participating physiotherapists achieved was 80.1 ± 6.5. The mean score showed correlations with both age (rs=0.9, p < 0.001) and clinical experience (rs=0.32, p < 0.001) of the physiotherapists. No significant differences were observed in the level of awareness of professional ethics codes between genders (p = 0.99) or among those working in private, public, or mixed sectors (p = 0.39).  Conclusion: Overall, the findings of this study indicate that the awareness level of Shiraz physiotherapists regarding the codes of professional ethics is generally good. However, certain codes may benefit from further training and emphasis.